Bridging the childhood epilepsy treatment gap in northern Nigeria (BRIDGE): Rationale and design of pre-clinical trial studies - Aliyu, Muktar H.; Kakooza, Angelina; Wheless, James; Wilmshurstr, Jo (Contemporary clinical trials communications, 2019)
Epilepsy is the most common serious childhood neurological disorder. In the low- and middle-income countries (LMICs) of Africa, children with epilepsy suffer increased morbidity and mortality compared to their counterparts in high-income countries, and the majority do not receive treatment - the childhood epilepsy treatment gap. Reports of the childhood epilepsy treatment gap in Africa are likely underestimates; most surveys do not include several common childhood seizure types, including most types of non-convulsive epilepsy. Efforts to scale up childhood epilepsy care services in the LMICs of Africa must contend with a shortage of physicians and diagnostic technology [e.g., electroencephalograms (EEGs)]. One pragmatic solution is to integrate epilepsy care into primary care by task-shifting to community health extension workers. The aims of this project (BRIDGE) are to: 1) train, develop, and pilot task-shifted epilepsy care teams; 2) develop and pilot innovative childhood epilepsy screening and diagnostic paradigms adapted to the local Hausa language/culture in Kano, northern Nigeria; and, 3) quantify and map the childhood epilepsy treatment gap, using geographic information systems (GIS), to target limited resources to areas of greatest need. Task-shifted teams will diagnose and manage childhood epilepsy using an innovative epilepsy screening tools and diagnostic and management paradigms in environments with limited EEG access. If validated and demonstrated efficacious in clinical trials, this project can be taken to scale across broader areas of west Africa's LMICs that share language and culture. BRIDGE has the potential to enhance access to basic childhood epilepsy care and establish the foundation for childhood epilepsy clinical trials in west Africa.
Keywords: Childhood epilepsy; Epilepsy treatment gap; Task shifting; Nigeria; Hausa